Numerical Simulation and Analysis of Diffusion Process for the Leakages of a Tunnel LNG Pipeline. (17th November 2020) - Kong, Chunyan; Zhang, Derong; Cai, Rong; Li, Shuangshuang; Zhu, Rongjun
Abstract : Taking a practical project as an example, based on the computational fluid dynamics (CFD), standard k- ε model and finite element method, a mathematical model for the diffusion due to liquefied natural gas (LNG) pipeline leakage in a tunnel was established, and the diffusion process was numerically simulated for three LNG leakage cases. From the simulation results, the variation of CH4 concentration field and explosive gas cloud with time within the tunnel, and the influence of leakage location on the diffusion was analyzed for the three cases. It was shown that the variation of CH4 concentration field had a similar trend for the three cases, but the CH4 explosive gas cloud length increased rapidly with the LNG leakage intensity so that dangerous situations would occur for the medium and large leakages, and a leak location closer to air inlet would lead to a more dangerous situation. When the amount of LNG leakage in the tunnel is large, the effect of mechanical ventilation is obviously weakened. Furthermore, a nitrogen seal precaution was proposed for the situations.